2013
DOI: 10.3109/13561820.2013.784729
|View full text |Cite
|
Sign up to set email alerts
|

Praxis and reflexivity for interprofessional education: towards an inclusive theoretical framework for learning

Abstract: While there is growing evidence of theoretical perspectives adopted in interprofessional education, learning theories tend to foreground the individual, focusing on psycho-social aspects of individual differences and professional identity to the detriment of considering social-structural factors at work in social practices. Conversely socially situated practice is criticised for being context-specific, making it difficult to draw generalisable conclusions for improving interprofessional education. This article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 21 publications
1
14
0
1
Order By: Relevance
“…Several studies found that students see the benefits of shared learning [45, 46], specifically medical students see the advantages at an early stage of their training [24, 30], followed by a decline in readiness for IPE [23, 24, 47]. Students who had undergone Shared Learning followed by an IP clinical placement had better attitudes or more readiness for IPE in comparison with only or no Shared Learning experience [23, 48].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies found that students see the benefits of shared learning [45, 46], specifically medical students see the advantages at an early stage of their training [24, 30], followed by a decline in readiness for IPE [23, 24, 47]. Students who had undergone Shared Learning followed by an IP clinical placement had better attitudes or more readiness for IPE in comparison with only or no Shared Learning experience [23, 48].…”
Section: Resultsmentioning
confidence: 99%
“…[30, 32, 40, 47, 49, 58, 61, 65] A post-intervention interview, focus group or writing assignment offers the student an opportunity to reflect on the interprofessional experience, as was done in 16 studies. [25, 27, 32, 34, 37, 4345, 51, 5355, 65, 69, 71, 72] More than 15 different instruments or their adaptations were applied in the 65 studies in this review (see Additional file 1). Twenty-one studies had student-led wards or standardized patients.…”
Section: Resultsmentioning
confidence: 99%
“…Gilligan, Outram, and Levett‐Jones () reported that the most memorable learning occurs during placement simulated IPE, which could be a logical opportunity. Dewey's theory of experientialism (Hutchings, Scammell, & Quinney, ) asserts that the meaning of an action is related to its consequences. Accordingly, experiencing the consequences of actions during a simulation in a safe environment could produce learning.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the nomological net of constructs pertinent to IPE training complements that of mindfulness 15. For example, constructs identified as impactful for IPE outcomes include reflexivity,16 openness to experience17 and experiential learning 18…”
Section: Introductionmentioning
confidence: 99%